Chemical and microbial qualities of morning and evening milk collected from selected dairy farms in Chittagong City of Bangladesh (Bangladesh Journal of Animal Science, 2016)
This study was undertaken to evaluate the nutritional and microbiological qualities of raw milk in the Chittagong City. Eighty samples of raw milk of cow were collected in the morning and evening from the surrounding farms of Chittagong Veterinary and Animal Sciences University (CVASU), Chittagong, Bangladesh. The results of compositional analysis evolved that fat, SNF, protein, lactose, specific gravity, freezing point  and mineral were (3.94±0.22%), (7.91±0.17%), (3.11±0.08%), (4.32±0.10%), (1.026±0.00), (-0.46±0.007), (0.68±0.01%), respectively. The fat% of evening milk was significantly higher (p0.001) than morning milk. Rest of the parameters were not significant. Microbiological enumeration revealed for the counts of total viable bacteria (cfu/ml) and coliform (cfu/ml) were 730500±639 and 280±1.36 in the morning milk and 628625±566 and 326±1.84 in the evening milk, respectively. The results of the current study indicated that the nutritional quality of evening raw milk was higher than in the morning raw milk.Bang. J. Anim. Sci. 2015. 44 (3):171-175